The growth of love - Keith J. White (Scottish Journal of Residential Child Care)
mentioned are Janusz Korczak, Paulo Friere and Friedrich Froebel. Recent research on cognitive development creates space for thinking about love, for example Sue Gerhardt, Why Love Matters (2004). The article concludes with reference to children in hospital and love in religious traditions, with a final mention of how Johannes Brahms saw love as the key to all of his music.